Cyberbullying: linguistic and legal challenges in the digital age - Потенко, Людмила Олександрівна; Потенко, Л. О.; Potenko, Liudmyla O. (Одеса : Фенікс, 2026)
The development of digital communications is giving rise to new challenges regarding the legal regulation of online speech. To effectively prevent cyberbullying and protect individuals in the Ukrainian digital space, it is necessary to strengthen forensic linguistic expertise, introduce specific legislation on cyberbullying, and enhance cooperation among all stakeholders. As Ukraine continues its path of European integration and digital resilience amid ongoing armed aggression, addressing these challenges through interdisciplinary research and practical measures becomes a matter of both individual security and national defense.
Potenko L. Cyberbullying: linguistic and legal challenges in the digital age. Соціально-політична та правова система України в цифрову епоху: сучасні виклики : матеріали Міжнар. наук.-практ. конф. (м. Одеса, 22 квіт. 2026 р.) : у 2-х т. / за заг. ред. С. Ківалова ; НУ «Одес. юрид. академія». Одеса : Фенікс, 2026. Т. 2. С. 572-574. URL: https://doi.org/10.32837/11300.33108
Keywords: булінг; кібербулінг; юридична лінгвістика; цифрова сфера; лінгвістична експертиза; bullying; cyberbullying; legal linguistics; digital sphere; forensic linguistic expertise